Cycling effects on transformation behaviour in shape memory CuZnAl alloys - Kayah, N; Cakmak, S; Artunc, E; Adiguzel, O (Editions Physique, 1995)
Shape memory alloys transform martensitically to close packed structures and have internally faulted structures in martensitic condition, and they are very sensitive to cycling and ageing effects. In noble metal copper based alloys, martensitic transformation occurs from a cubic structure with B2 (or DO3) order to a long period layered structure 9R (or 18R). In a single crystal of parent phase, 24 martensite variants grouped around six {110}(infinity) matrix planes can be formed at temperatures below M(s). These alloys deform by variant transformations, in case they are stressed in the martensitic condition. Cycling effects on transformation behaviour in two shape memory CuZnAl alloys received in the closed-coil form called shape memory actuator which have originally open-coil form in austenitic condition have been investigated. Shape memory alloys remain in the deformed shape in martensitic condition and recover the original form in austenitic condition and the shape memory actuators cycle between the open and closed-coil configurations on heating above A(f) and cooling below M(f) temperatures. These effects are attributed to the reversible transition between the austenite and martensite phases. These alloys are metastable in martensitic condition, and cycling effects also contribute to the martensite stabilization.
International Conference on Martensitic Transformation (ICOMAT 95) -- AUG 20-25, 1995 -- LAUSANNE, SWITZERLAND
Keywords: Martensite Variants; Stress